Konsep 'Ibu Pertiwi' sebagai Landasan Inkulturasi Ekologi Integral Gereja Katolik di Indonesia - Thersiani Bheka; Intansakti Pius X (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2025)
This article responds to the challenge of contextualizing Laudato Si's teachings on integral ecology in the Indonesian Catholic Church. This study examines the concept of "Mother Earth" as a symbol of local wisdom that has the potential to be used as a theological foundation in the inculturation process. Through textual analysis and theological-contextual reflection, this qualitative research explores the meaning of "Mother Earth" as the personification of the earth and dialogues it critically with integral ecological principles. The results of the study show that the values of harmony, mutual cooperation, and respect in the concept of "Mother Earth" have a deep compatibility with the vision of Laudato Si'. This symbol of integration not only strengthens contextual ecological spirituality, but also gives birth to praxis implications in the form of liturgical models, catechesis, and ecologically minded community assistance. In addition, the integration of local values provides space for the people to understand the relationship between humans and nature as a unit that supports each other, not as a relationship of exploitation. This approach opens up opportunities for the formation of ecological consciousness that is rooted in the nation's culture and is in harmony with the teachings of the universal Church. Thus, the inculturation based on "Mother Earth" offers a model to deepen the role of the Church in building a civilization of love in Indonesia and strengthen the collective commitment to environmental sustainability.